On the dynamics of a collapsing bubble in contact with a rigid wall. (10th October 2022) - Saini, Mandeep; Tanne, Erwan; Arrigoni, Michel; Zaleski, Stephane; Fuster, Daniel
Abstract: Abstract : This work reveals that the dynamic response of a spherical cap bubble in contact with a rigid wall depends on the effective contact angle at the instant prior to collapse. This parameter allows us to discriminate between two regimes in which the mechanisms of interaction between the collapsing bubble and its surrounding medium differ significantly: when the contact angle is smaller than 90^° , a classical jet directed towards the wall is observed, whereas if the initial contact angle is larger than 90^° , an annular re-entrant jet parallel to the wall appears. We show that this change of behaviour can be explained using the impulse potential flow theory for small times, which shows the presence of a singularity on the initial acceleration of the contact line when the contact angle is larger than 90^° . Direct numerical simulations show that although viscosity regularises the solution at t > 0, the solution remains singular at t=0 . In these circumstances, numerical and experimental results show that the collapse of flat bubbles can eventually lead to the formation of a vortex ring that unexpectedly induces long-range effects. The role of the bubble geometry at the instant of maximum expansion on the overall collapse process is shown to be well captured by the impulse potential flow theory, which can be generalised easily to other bubble shapes. These results may find direct application in the interpretation of geophysical flows as well as the control and design of biomedical, naval, manufacturing and sonochemistry applications.